Sorption of BB41 dye molecules using chitosan based particles from aqueous solutions: A kinetic and thermodynamic evaluation - Demirtas, Hulya; Tasar, Seyda; Kaya, Fatih; Ozer, Ahmet (Elsevier Sci Ltd, 2022)
In this study, starting from chitosan is a hydrophilic polymer with positively charged, it was aimed to produce chitosan-based particles and to be evaluated as a sorbent. Chitosan-based polymeric particles production was carried out by the precipitation-collection method from chitosan. Chitosan and chitosan-based sorbent were characterized. For this purpose, SEM and FTIR analyzes were used. Sorption activities of the chitosan-based polymeric particles were investigated for basic dye (basic blue 41, BB41). The effect of various sorption parameters (temperature, initial pH value, chitosan amount, initial dye concentration, contact time, etc.) on the sorption efficiency of BB41 dye molecules was investigated. The optimum sorption conditions were determined. The optimum temperature of solution, initial pH value, chitosan amount, contact time and initial BB41 dye concentration were determined as 25 degrees C, 10.5 +/- 0.02, 1 g/L, 240 min and 50 ppm, respectively. Sorption capacities at 25, 35, 45, and 55 celcius were determined as 1.710, 1.410, 1.360, and 1.200 mg/g, respectively. In addition, the sorption yields were determined as 85.00%, 73.21%, 67.86%, and 60.00%, respectively. Experimental results were evaluated by applying Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich's (DR) isotherm models. It was determined that the obtained data fit well with the Langmuir isotherm model. The maximum sorption capacity (qmax) was calculated to be 1.920 mg/g. To calculate kinetic parameters, pseudofirst-order, pseudo-second-order, Elovich, and intraparticle diffusion kinetic model equations were used in the study. It was determined that the pseudo-second-order model was better suited to explain the experimental data. Using the pseudo-second-order kinetic model equation, the maximum sorption capacities (qc,h) for 25, 35, 45, and 55 degrees C were calculated to be 1.720, 1.490, 1.380, and 1.240 mg/g, respectively. It was determined that the desorption activities of chitosan particles were over 99.5%. The chitosan particles retained their physical stability under the specified desorption conditions. It was decided that it was a suitable sorbent for reuse.
Keywords: Chitosan; Polymeric particle; Sorption; Basic blue 41; Kinetic and thermodynamic evaluation